L’évolution du taux de la plus-value en France (1951-1980) - Delaunay, J.-C. (L'Actualité économique, 1981)
ABSTRACTThe measurement of the rate of surplus-value, in France, during the last thirty years, refers to the Marxist economic theory of capitalism and araises theoretical and statistical problems. From a theoretical point of view and after discussing on the legitimacy of measuring the rate of surplus-value, the author mainly evocates the following problems. 1) what kind of workers generate surplus-value? 2) are engineers producers of surplus-value? 3) is it correct to use the data of national accounts to quantify a rate defined on an essential level? After mentioning the theoretical choices, the author examines the statistical aspects of the problems. According to his results and assumptions, his main conclusion is that the rate of surplus-value, in France, has grown up from 1950. But its rate has been getting slower and slower. The return of capitalist exploitation would have been decreasing. The economic policy worked out from 1974 to 1980 resulted in an increase of the rate of surplus-value without reaching the variations observed during the Vth Républic.